2022
DOI: 10.1007/s13304-021-01212-2
|View full text |Cite
|
Sign up to set email alerts
|

The real-word impact of breast and colorectal cancer surgery during the SARS-CoV-2 pandemic

Abstract: The postponing of screening and the health care system reorganization, due to the Covid-19 pandemic and lockdown, could led to a concerning decline in breast and colorectal cancer diagnoses. This monocentric retrospective analysis has compared the pre-Covid period (March 2019 to March 2020) to the Covid period (April 2020 to April 2021) in terms of screening programs, clinical, surgical and pathological. A total of 799 patients diagnosed with Breast Cancer (BC) and Colorectal Cancer (CRC) underwent surgery dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 1,349 potentially eligible records, of which 46 articles were reviewed in full. In addition to our study, 13 studies ( 1 , 12 , 21 31 ) published between 2020 and 2022 were included for analysis. The details of the 14 eligible studies are presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies ( 1 , 21 , 22 , 24 27 , 29 , 31 ) reported on postoperative mortality. There was no statistically significant difference [OR, 0.90; 95% confidence interval (CI), 0.80, 1.01; p = 0.07] ( Figure 1 ) in the overall incidence of postoperative complications between patients in the COVID-19 pandemic group and those in the pre-COVID-19 pandemic group, with low heterogeneity between studies (I 2 = 26%, p = 0.22).…”
Section: Resultsmentioning
confidence: 99%
“…on CRC screening differs by country 14 , which may be due to the stringency of lockdown policies by country, among other factors. In Korea, it was reported that there was no CRC stage upshifting during the COVID-19 pandemic in the early days of the pandemic 15 .…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…much evidence has already been reported worldwide of the negative impacts of the pandemic on cancer diagnosis and treatment 4,13,14,22 . Because cancer patients tend to travel to other areas for the purpose of cancer treatment 23 , the damage caused by movement restrictions or social distancing during the pandemic period will be larger than other diseases.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%